Role of NH(2)- and COOH-Terminal Domains of the P Protein of Human Parainfluenza Virus Type 3 in Transcription and Replication - De, Bishnu P. (American Society for Microbiology, 2000)
The phosphoproteins (P proteins) of paramyxoviruses play a central role in transcription and replication of the viruses by forming the RNA polymerase complex L-P and encapsidation complex (N-P) with nucleocapsid protein (N) and binding to N protein-encapsidated genome RNA template (N-RNA template). We have analyzed the human parainfluenza virus type 3 (HPIV3) P protein and deletion mutants thereof in an in vitro transcription and in vivo replication system. The in vitro system utilizes purified N-RNA template and cell extract containing L and P proteins coexpressed via plasmids using a recombinant vaccinia virus expression system. The in vivo system takes advantage of minigenome replication, which measures luciferase reporter gene expression from HPIV3 minigenomes by viral proteins in a recombinant vaccinia virus expression system. These studies revealed that the C-terminal 20-amino-acid region of P is absolutely required for transcription in vitro and luciferase expression in vivo, suggesting its critical role in viral RNA synthesis. The N-terminal 40-amino-acid region, on the other hand, is essential for luciferase expression but dispensable for transcription in vitro. Consistent with these findings, the C-terminal domain is required for binding of P protein to the N-RNA template involved in both transcription and replication, whereas the N-terminal domain is required for the formation of soluble N-P complex involved in encapsidation of nascent RNA chains during replication. Coimmunoprecipitation analysis showed that the P protein forms a stable homooligomer (perhaps a trimer) that is present in L-P and N-P complexes in the higher oligomeric forms (at least a pentamer). Interestingly, coexpression of a large excess of N- or C-terminally deleted P with wild-type P had no effect on minigenome replication in vivo, notwithstanding the formation of heterooligomeric complexes. These data indicate that P protein with a deleted terminal domain can function normally within the P heterooligomeric complex to carry out transcription and replication in vivo.